Efficient study on the influence of compressor casing configuration on aeroelastic stability using multi-passage energy method - Xin Zhao; Le Han; Dasheng Wei (Propulsion and Power Research, 2025)
This study investigated the influence of casing profiles on the aeroelastic stability of a transonic compressor rotor. To elucidate the influence of casing profiles on aerodynamic damping (AD) and delve into more detailed insights, the influence coefficient method and phase-shift theory were incorporated into the conventional energy method to establish the multi-passage energy method. The unsteady pressure was calculated using the influence coefficient method and the outcomes at various nodal diameters (NDs) were reconstructed based on the phase-shift theory. Thus, the multi-passage energy method offers more comprehensive information than the conventional energy method, the aeroelastic eigenvalue method, and the coupled fluid-structure interaction method. Four casing profiles were simulated. In contrast to the straight casing configuration, the concave shrinking casing was found to be detrimental to aeroelastic stability. The convex shrinking casing can alleviate the blockage in the tip flow field and improve both the aerodynamic performance and aeroelastic stability. The multi-passage energy method further revealed that the AD is contributed by the blade itself and the adjacent blades. In comparison to the straight casing, the convex shrinking casing not only enhances the AD of the blade itself but also diminishes the AD fluctuation of the adjacent blades. Consequently, the minimum AD is increased.